Ukraine : Request for Stand-by Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion, and Statement by the Executive Director for Ukraine. (IMF Staff Country Reports; Country Report ;, 2008)
The staff report for the Request for a Stand-by Arrangement with officials of Ukraine discusses economic developments and policies. Assuming a global recovery in the second half of 2009, the Ukrainian economy could be back at its estimated potential growth rate by 2011. The large financing gaps owing to debt rollover complications can only be partially met by substantial domestic adjustment and funding from other sources. There is a presumption that exceptional access in capital account crises will be provided using resources of the Supplemental Reserve Facility (SRF).